2008
DOI: 10.2989/ajar.2008.7.2.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical waste management in the context of the Kanye community home-based care programme, Botswana

Abstract: This study examines clinical waste disposal and handling in the context of a community home-based care (CHBC) programme in Kanye, southern Botswana. This qualitative study involved 10 focus group discussions with a total of 82 HIV/AIDS primary caregivers in Kanye, one-to-one interviews with the five nurses supervising the programme, and participant observation. Numerous aspects of clinical or healthcare waste management were found to be hazardous and challenging to the home-based caregivers in the Kanye CHBC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…This presents a human rights abuse and dilemma, as those who take care of others face risk from their volunteering occupations. 35 Literature abounds on the fact that a number of diseases and infections, including HIV infections, have been documented to be transmitted by mere contact with the body fluids and secretions of patients, and hospital waste abounds in substances soiled with the body fluids and secretions of patients suffering from such diseases. Unskilful handling and disposal of clinical or hospital waste could also be catastrophic to the health and wellbeing of the community.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…This presents a human rights abuse and dilemma, as those who take care of others face risk from their volunteering occupations. 35 Literature abounds on the fact that a number of diseases and infections, including HIV infections, have been documented to be transmitted by mere contact with the body fluids and secretions of patients, and hospital waste abounds in substances soiled with the body fluids and secretions of patients suffering from such diseases. Unskilful handling and disposal of clinical or hospital waste could also be catastrophic to the health and wellbeing of the community.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…36 Other studies have found that the management and disposal of clinical waste in many care programmes have continued to be a thorn in the flesh of the caregivers. 35,37,38 This is due either to a lack of policy, or the failure to operationalise it, inadequate community education on the subject, neglect, and a lack of adequate facilities, leading to unprofessional and ineffective ways of disposal and handling. This has borne grave hazards that compromise the quality of care in the programmes.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would possibly mean some of the desperate caregivers would have to wash their clients without any protective clothing. This exposes them to the challenge of infection (Kang"ethe, 2008). It is recommended that the government, working in collaboration with the CHBC authorities, institute and intensify monitoring and evaluation of the programme and ensure that the programme has adequate care package to ensure quality care giving.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…These tasks include household chores, subsistence farming or other casual employment and looking after children, elderly people and other dependants. It is also common for such caregivers taking care of infected husbands or babies to contract the disease themselves, causing their health to deteriorate while they are expected to care for everyone else (Jackson, 2002;Kang"ethe, 2006bKang"ethe, , 2008. This article will discuss the importance of providing incentives to raising the morale and level of motivation and therefore the productivity of care programmes in Botswana.…”
Section: Introductionmentioning
confidence: 99%